A Critical Review of Traditional Ecological Knowledge (TEK) in Science Education. Issue 4 (2nd October 2017) - Kim, Eun-Ji Amy; Asghar, Anila; Jordan, Steven
ABSTRACT: What is traditional ecological knowledge? In many disciplines, including science education, anthropology, and resource management, it has been conflated with Indigenous knowledges, which has contributed to misunderstandings. This article explores the history of traditional ecological knowledge and examines its contemporary conceptualizations in science education. We argue that traditional ecological knowledge and Indigenous knowledges are distinct, emphasizing that traditional ecological knowledge is a form of cultural and intellectual appropriation that modifies Indigenous knowledges to better fit a conventional Western modern science framework. Our article explores how contemporary understandings of traditional ecological knowledge have shaped the development of science education curricula.